Propuesta de Implementación de un sistema automatizado para disipación de calor en la planta Comestibles El Gaván - Herrera Roncancio, Mariana del Pilar (Universidad Antonio Nariño, 2021)
In a rice brad production plant in the municipality of Restrepo- Meta, a proposal is proposed for the implementation of an automated system that allows the heat dissipation generated by the furnace equipment, sealing and packaging machines, among others, which are part of the production to the Comestibles El Gaván plant. With the results of thermal comfort measurements, the action plan for the proper engineering controls was drawn up. Taking into account the duties and obligations of companies or employers whit their collaborators, as is it is, to provide the best conditions to develop work activities.The El Gavan production plant works with a storage warehouse, and machinery that converts the raw material into rice bread donuts and other similar products, which are going to be packed, which implies the operation of human resources that participate in the preparation of five thousand (5000) daily packages. The personnel involved in these processes are exposed to high temperatures that exceed 45 °, which is why the implementation of a heat sink was proposed to have a suitable environment for the people who work in the plant. Thus, avoiding a significant decrease in production due to cuts due to potholes that workers make to take breaks due to the heat of the work site, this extends the hours to meet the daily goal generating more operational expenses.